Penggunaan Terapi Musik Untuk Meningkatkan Kemampuan Pemahaman Kosakata Pada Anak Tuna Grahita Kelas Dasar IV SLB-C Katolik Santa Anna Tomohon - Usman Duyo (Peneliti.net, 2021)
This study aims to see the ability of mentally retarded children in understanding vocabulary. This research is a qualitative research with a case study research strategy in the form of observations and interviews with several informants, as data collection that can support the research process. This study uses music therapy. The researcher and the subject sang together and listened to several songs where the lyrics of the song became an aspect of collecting data about increasing vocabulary skills of the students who were the research subjects. The research uses several tools to support the research process such as guitars and cellphones. This research was conducted at SLB – C Catholic Santa Anna Tomohon. Based on data analysis, it can be stated that the ability to understand vocabulary increases after singing the songs that are trained on children. Every sentence in the song that is sung, the child is able to improve the sentences in the song. This proves that the research hypothesis is accepted. The hypothesis is that music activities can improve the vocabulary skills of mentally retarded children at SLB-C Catholic Santa Anna Tomohon